“Turning A New Leaf” Development of Spectroscopic Protocols to Study Plant Health - Khambatta, Karina (Curtin University, 2022)
Improved methods to monitor plant health may be pivotal for future protection of crops from disease and environmental stressors. Epicuticular waxes, and macronutrients (K+ and Ca2+) hold important physiological functions within plants, and are therefore, excellent markers of plant health. This thesis has developed new spectroscopic analytical methods to directly image changes in epicuticular waxes and Ca2+ and K+ on plant leaves, for future application to monitor plant health.